Pengembangan Aplikasi Manajemen Data Etnofarmakologi Menggunakan Unified Modeling Language - Mariana Purba (JSAI (Journal Scientific and Applied Informatics), 2025)
This research aimed to develop an ethnopharmacology data management application designed using Unified Modeling Language (UML) for system modeling. The application focused on managing data related to medicinal plants and their usage in ethnopharmacology. UML, as a standard modeling language, was used to visualize and document the artifacts of the software system, which could meet the needs of ethnopharmacology data management in a structured and efficient manner. UML allowed developers to identify and define system elements and their relationships within diagrams. The results of this research showed that the use case for the ethnopharmacology data management application involved four main actors: reader, data manager, author, and reviewer. The data manager actor was responsible for user management and the approval of ethnopharmacology data, while the author actor played a role in managing and submitting ethnopharmacology data for approval. The reviewer actor was responsible for reviewing the approved ethnopharmacology data. The use case diagram also included include and extend relationships, showing the interconnections between various use cases such as medicinal plant data, ethnopharmacology usage data, ethnopharmacology ingredients data, and medicinal plant part image data.